Crossing Borders on Cross Border Car Mobility - Frank Witlox; Veronique van Acker (European Journal of Transport and Infrastructure Research, 2012)
“We live in a world of lines and compartments. We may not necessarily see the lines, but they order our daily life practices, strengthening our belonging to, and identity with, places and groups, while - at one and the same time - perpetuating and reperpetuating notions of differences and othering.” (Newman, 2006, p. 143)